From research to action: Oral Misoprostol for preventing postpartum haemorrhage during home delivery in rural Bangladesh - Rana, Md Masud; Gisby, Laura Jane; Mamun, Md Abdullah Al (South East Asia Journal of Public Health, 2015)
While Bangladesh has experienced a remarkable 40% decline in maternal mortality over the past ten years, it remains a major health problem. Postpartum haemorrhage (PPH) is one of the most prevalent preventable causes of maternal mortality in the country, accountable for over a quarter of the deaths. In Bangladesh, over 70% of the births take place outside health centres, mostly in poor rural areas. This leads to lack of access to conventional injectable uterotonics (i.e. oxytocin) during the third stage of labour to prevent or treat PPH. The purpose of this paper is to discuss the use of oral misoprostol as an intervention to prevent PPH in rural Bangladesh during home births that take place without trained birth attendants. A review of the existing literature in electronic database, shows robust evidence from Randomised Controlled Trials (RCTs)on the effectiveness of oral misoprostol in preventing PPH. Misoprostol has proved significantly effective (RR 0.58, CI 0.380.87) in reducing PPH incidence and to go have a very good safety profile. Furthermore, field trials and operational studies have already proven the feasibility, acceptance and safety of scaling up the use of misoprostol in rural Bangladesh. Therefore, we recommend oral misoprostol to be included in the National Maternal Health Strategy as an intervention to control PPH during home birth in rural Bangladesh. South East Asia Journal of Public Health Vol.4(2) 2014: 2-6